Recurrent Reversible Carotid Dissection in Antiphospholipid Syndrome: A Case Report and Systematic Review of Vasculopathic Mechanisms - Javed, Muhammad Athar; Ahmad, Saima; Cheema, Naila Amjad; Pervaiz, Nida (Journal Of Cardiovascular, Neurovascular & Stroke, 2025)
Antiphospholipid syndrome (APS) is increasingly recognized as a potential cause of cervical artery dissection, although the association remains underreported and poorly understood. We present a rare case of recurrent reversible internal carotid artery dissection in a patient with APS and systematically review current evidence regarding the pathophysiological mechanisms, clinical presentations, and management approaches. Our findings suggest that APS-related vasculopathy may predispose to arterial wall fragility and dissection through multiple mechanisms, including endothelial dysfunction, hypercoagulability, and altered vascular remodeling. Importantly, APS-associated dissections may demonstrate a higher potential for reversibility and recurrence compared to dissections of other etiologies, likely reflecting the dynamic nature of immune-mediated vascular injury rather than traditional atherosclerotic or traumatic causes. Recognizing this distinct entity is critical for appropriate management and prevention strategies in this population.